IoT Security Attacks on the Public Sector: Systematic Literature Review - Fandan Dwi Nugroho Wicaksono; Winny Purbaratri; Moch Fajar Purnomo Alam; Agnes Novita Ida Safitri (Komunitas Dosen Indonesia, 2024)
The primary objective of this study is to examine security threats that specifically target the Internet of Things (IoT) used in the Public Sector. This sector is widely acknowledged as a crucial element of the fourth industrial revolution. The high volume of intelligent devices employed in the public sector, which are linked in the Internet of Things (IoT), and each of them transmits sensitive data in numerous instances, makes security of utmost importance. The objective of this study is to categorize various forms of security attacks and propose strategies to mitigate security breaches through many approaches. This study employed a systematic review, which is a methodical examination of current literature. The data synthesis methodology in this study consisted of comparing 15 literature sources that had been evaluated for quality and satisfied the specified criteria for inclusion and exclusion. The utilized database sources include renowned platforms such as Scopus, ACM, and IEEE. The present study employs a qualitative methodology, specifically utilizing the perspectives of two information security specialists to examine the existing literature. The findings of this study have made a meaningful contribution to the field of public sector. This study categorizes four types of assaults against Public Sector IoT: 37% Denial-of-Service (DoS) attacks, 31% Malware attacks, and 19% Phishing attacks. System attacks account for 13% of all system attacks. By contrast, 50% of the security attack mitigation strategies rely on authentication, 36% on Secure Communication, and 14% on Application Security.